On Estimation of Point-in-Time Loss Given Default : A Comparative Study - Kuchta, Michal; Janíčko, Martin, 1983-; Miklánek, Tomáš; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2018)
This Thesis deals with the new provisioning standard IFRS9, in the specific case of LGD modelling and proposes a set of robust approaches to meet the Standard's requirements. It compares the scenario generation through conditional forecasting in DSGE with the proposed pioneering methodology endogenizing scenario paths and their probabilities in Bayesian Markov-switching VAR. It develops a range of recovery rate models using survival analysis and principal component regression. Sub-results are then integrated to derive single probability-weighted ECL estimate.
Vedoucí práce: Martin Janíčko
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses